next up previous
Next: Perturbed planetary orbit Up: Derivation of Gauss planetary Previous: Derivation of Gauss planetary


Unperturbed planetary orbit

Consider a planet (say) of mass $ m$ and relative position vector $ {\bf r}$ that is orbiting around the Sun, whose mass is $ M$ . The planet's unperturbed equation of motion is written (see Section 4.16)

$\displaystyle \ddot{{\bf r}} + \mu\,\frac{\bf r}{r^{\,3}} = {\bf0},$ (I.1)

where $ \mu= G\,(M+m)$ . As described in Chapter 4, the solution to this equation is a Keplerian ellipse.

Let $ x$ , $ y$ , $ z$ be a Cartesian coordinate system in a reference frame whose origin corresponds to the location of the Sun, and which is such that the planet's unperturbed orbit lies in the plane $ z=0$ , with the angular momentum vector pointing in the positive $ z$ -direction, and the perihelion situated on the positive $ x$ -axis. Let $ r$ , $ \theta $ , $ z$ be a cylindrical coordinate system in the same reference frame.

We know from the analysis of Chapter 4 that

    $\displaystyle {\bf r}$ $\displaystyle = r\,{\bf e}_r,$ (I.2)
and   $\displaystyle \dot{\bf r}$ $\displaystyle = \skew{5}\dot{r}\,{\bf e}_r + r\,\skew{5}\dot\theta\,{\bf e}_\theta,$ (I.3)

where $ {\bf e}_r=(\cos\theta,\,\sin\theta,\,0)$ and $ {\bf e}_\theta = (-\sin\theta,\,\cos\theta,\,0)$ . Moreover, the planet's mean orbital angular velocity is

$\displaystyle n= \left(\frac{\mu}{a^{\,3}}\right)^{1/2};$ (I.4)

its orbital energy per unit mass is

$\displaystyle {\cal E} = -\frac{\mu}{2\,a};$ (I.5)

its orbital angular momentum per unit mass is

$\displaystyle {\bf h} = {\bf r}\times \dot{\bf r} = h\,{\bf e}_z,$ (I.6)

where

$\displaystyle h \equiv r^{\,2}\,\skew{5}\dot{\theta} = (1-e^{\,2})^{1/2}\,(\mu\,a)^{1/2};$ (I.7)

and its eccentricity vector is

$\displaystyle {\bf e} \equiv \frac{\dot{\bf r}\times {\bf h}}{\mu} - \frac{{\bf r}}{r} = e\,{\bf e}_x.$ (I.8)

Here, $ a$ and $ e$ are the planet's orbital major radius and eccentricity, respectively. Note that, for the unperturbed orbit, the quantities $ a$ , $ e$ , $ n$ , $ {\cal E}$ , $ {\bf h}$ , and $ {\bf e}$ are all constant in time. We also have

    $\displaystyle r$ $\displaystyle = \frac{a\,(1-e^{\,2})}{1+e\,\cos\theta}=a\,(1-e\,\cos E),$ (I.9)
    $\displaystyle \skew{5}\dot{r}$ $\displaystyle = \frac{h\,e\,\sin\theta}{a\,(1-e^{\,2})}=\frac{h\,e}{a\,(1-e^{\,2})^{1/2}}\,\frac{\sin E}{1-e\,\cos E},$ (I.10)
    $\displaystyle \cos E$ $\displaystyle = \frac{\cos\theta+e}{1+e\,\cos\theta},$ (I.11)
    $\displaystyle \sin E$ $\displaystyle = \frac{(1-e^{\,2})^{1/2}\,\sin\theta}{1+e\,\cos\theta},$ (I.12)
and   $\displaystyle E - e\,\sin E$ $\displaystyle = {\cal M},$ (I.13)

where $ \theta $ , $ E$ , and $ {\cal M}$ are the planet's true anomaly, eccentric anomaly, and mean anomaly, respectively. (See Chapter 4.)


next up previous
Next: Perturbed planetary orbit Up: Derivation of Gauss planetary Previous: Derivation of Gauss planetary
Richard Fitzpatrick 2016-03-31